Framework for mobility model detection based on local information - PENG Min; HONG Pei-lin; LU Han-cheng; XUE Kai-ping (Tongxin xuebao)
In order to get the real-time mobility model information which could be exploited to assist routing decision,a framework for mobility model detection based on local information（FMDL） was proposed.In FMDL,each node collected the local information on connectivity through neighbor discovery mechanism and generated the connectivity matrix.The changing rule of relative position could be extracted from the connectivity matrix,and then the real-time mobility model was detected.The simulation results show that FMDL achieves high detection rate without any auxiliary equipment.